High effectiveness of platinum complexes with adamantylamine in overcoming resistance to cisplatin and suppressing proliferation of ovarian cancer cells in vitro - Horváth, Viktor, 1978- (2006)
Currently, platinum-based drugs (cisplatin and carboplatin) remain still the most important conventional cytotoxic agents used in 1st-line combination chemotherapy protocols for treating ovarian cancer patients with overall response rate exceeding 80 % when integrated with cytoreductive surgery. However, despite widespread clinical use and strong antitumor activity of cisplatin, its effects are often decreased due to intrinsic or acquired resistance. The resistance of tumor cells to cisplatin remains a major cause of treatment failure in cancer patients. Moreover, cisplatin therapy can lead to a number of side effects such as nephrotoxicity, neurotoxicity, and emetogenesis. The toxicity of cisplatin limits the dose that can be given to patients. These facts together with the aim to find platinum-based derivatives with higher antitumor activity, displaying more tolerable toxicological profile and overcoming resistance in many tumor types have led many investigators to attempt the synth.